A novel Nb2S4 complex with a dithiophosphinate ligand: Synthesis, structure and redox properties. (15th January 2019) - Gushchin, Artem L.; Rogachev, Alexander V.; Fomenko, Iakov S.; Romashev, Nikolay F.; Nadolinny, Vladimir A.; Abramov, Pavel A.; Laricheva, Yuliya A.; Sokolov, Maxim N.
Graphical abstract: The first Nb2 S4 dithiophosphinate complex, [Nb IV Nb IV S4 (S2 P i Bu2 )4 ] (1 ), has been synthesized. Remarkably, cyclic voltammetry of1 displays two chemically reversible niobium-centered one-electron oxidation processes. The one-electron oxidation product [Nb V Nb IV S4 (S2 P i Bu2 )4 ] + (1 + ) was prepared in situ and characterized by EPR. Abstract: A new diisobutyldithiophosphinate complex, [Nb2 S4 (S2 P i Bu2 )4 ] (1 ), was obtained by a ligand substitution reaction using (Bu4 N)4 [Nb2 S4 (NCS)8 ] and NaS2 P i Bu2 ·3H2 O. Its crystal structure has been determined. The NbNb distance is 2.9034(7) Å. The cyclic voltammogram (CV) of1 in dichloromethane exhibits two successive chemically reversible one-electron oxidation waves at +0.55 and +1.10 V (versus Ag/AgCl) attributed to the Nb IV /Nb V couple. This is the first Nb2 S4 cluster that shows two reversible oxidations. The paramagnetic mixed-valence Nb(IV/V) product of the one-electron oxidation, [Nb2 S4 (S2 P i Bu2 )4 ] + (1 + ), was generated in situ . The EPR spectrum of1 + in acetonitrile reveals a 19-line signal arising from the hyperfine interaction between the unpaired electron and two equivalent 93 Nb nuclei with I = 9/2, indicating complete delocalization of the unpaired electron over both metal centers. DFT calculations have been performed for the complexes [Nb2 S4 (S2 PMe2 )4 ], [Nb2 S4 (S2 P(OMe)2 )4 ], [Nb2 S4 (S2 CNMe2 )4 ] and [Nb2 S4 (S2 COMe)4 ] and their single and double oxidized species in order to explain the peculiarities of their redox behavior. The results show that the HOMOs responsible for oxidation have a predominantly metallic character in all cases, but they are significantly more high-lying for the dithiophosphinate and dithiocarbamate complexes, which explains their ability to be oxidized.